The comparative values of foxtail willet seed and shelled corn for fattening spring pigs on alfalfa pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
In order to fatten pigs economically it is necessary to feed a large amount of concentrates in the form of grain and protein supplements. Corn is the grain usually employed. When the price of corn becomes very high in relation to other feeds, hog feeders look about for a substitute. In recent times corn has been high in price, and occasionally impossible to purchase. This was the situation a year ago when a purchase of Foxtail Millet seed was made to replace corn. With this seed on hand it was thought advisable to carryon a feeding trial to compare it with corn in efficiency, as the state might be in a position sometime to grow considerable millet. The information thus obtained would then be available and valuable to the swine feeder.
Keywords: Swine; Nutrition; Foxtail willet seed; Corn; Alfalfa pasture